Analisis Wacana Van Dijk dalam Program Pengarusutamaan Gender di RRI Jember - Wulandari, Cahyani; Jannah, Siti Raudhatul (Icon: Islamic Communication and Contemporary Media Studies, 2023)
This study reviews one of the Gender Mainstreaming programs at RRI Jember, because there has never been any previous research at RRI Jember and the material is often found in the surrounding life. The focus of this research: 1) what languages ​​do broadcasters use to broadcast the Gender Mainstreaming (PUG) program at RRI Jember? 2) What communication measures are used by the broadcaster of RRI Jember to support the Gender Mainstreaming (PUG) program? The aims of this research are: 1) to find out what language broadcasters use in the Gender Mainstreaming (PUG) program at RRI Jember. 2) to find out the communication actions taken by broadcasters in supporting the objectives of the Gender Mainstreaming (PUG) program at RRI Jember. This research method uses descriptive qualitative media text with Van Dijk's discourse model. The data collection techniques using observation, interviews and documentation. The results of this study: 1) the broadcast of the Gender Mainstreaming program reviewed the analysis of Van Dijk's discourse text, the language used by the RRI Jember broadcaster, there was a tendency to favor a woman who had to raise her dignity by using language that was accessible, and acceptable to listeners/audiences listening to the broadcast. RRI Jember. 2) in terms of Van Dijk's critical structure, the researcher concludes that the communication actions taken by the broadcaster RRI Jember in supporting the Gender Mainstreaming program are very good and implemented. In addition to communication actions, RRI Jember broadcasters also carry out actions carried out in daily life.